Memperkuat Kesadaran Bela Negara dengan Nilai-Nilai Pancasila dalam Perspektif Adat Papua - Kustiyanti Kustiyanti (FKIP, Universitas Palangka Raya, 2022)
State defense awareness is an important aspect of maintaining the sovereignty and integrity of the nation. In Papua, Pancasila values and local customs have a central role in building this awareness. The core of the research is to explore how Pancasila values are integrated with Papuan local wisdom to strengthen state defense awareness. The method in this research is a qualitative study combined with an ethnographic approach to understand the interaction between Pancasila values and Papuan customs. The results show that strengthening state defense awareness in Papua can be achieved through education based on local values and Pancasila, as well as active community participation in protecting culture and the environment.